New hybrid organizations creating bridges through innovative educational solutions: The case of Hilversum Media Campus, the Netherlands. Issue 4 (August 2022) - Borges da Costa, Sunamita Iris Rodrigues; Lodders, Johannes WE
Disruptive technologies and services created a new paradigm that changed the way media were created, threatening traditional media organizations. Many media companies have been challenged to respond to new types of media formats, productions and channels, for which they have needed new talents with the right skills and space to experiment. This paper presents the case of the Hilversum Media Campus (HMC) in the Netherlands, a hybrid organization created by a Triple Helix cooperation to develop the new talents necessary to maintain Het Media Park as an economic regional center and for the country's media industry. This article reflects on the role of hybrid organizations as connection centers of actors, knowledge and interests; discusses the emergence of a new paradigm and its effects on the media sector; and reconstructs the history of the HMC, its conceptualization and structuring, its processes and the results achieved. In the case analysis, certain factors stood out with regard to the results achieved: the research into stakeholders' ambitions and interests, which led to a defined strategy and targeted actions; the business model construction, with parties having to contribute financially; the allocation of means, bringing energy and focus to the supported deliverables; and the autonomy of the HMC.